FINE ART AND ITS NATURE, TYPES AND GENREES (Uzbek Scholar Journal, 2023)
This article provides information about the current role of fine arts and the fine arts and its essence, types and genres. The fact that an artist does not know the types and genres of the field in which he works in the field of fine arts is a sign that he cannot be a true creator of fine arts.